2021
DOI: 10.1111/and.14338
|View full text |Cite
|
Sign up to set email alerts
|

L‐carnitine added to post‐thawed semen acts as an antioxidant and a stimulator of equine sperm metabolism

Abstract: Many high-performance stallions have low-quality frozen semen.Thus, strategies to improve the quality of post-thawed semen before artificial insemination are of great interest to increase the fertility of those animals. During the semen freezing process, equine spermatozoa are more prone to oxidative stress because a large portion of the seminal plasma is discarded after centrifugation (Brinsko et al., 2000). This results in an imbalance in seminal plasma antioxidants, reactive oxygen (ROS) and nitrogen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The protective effects of LC are due to its antioxidant properties which work as scavengers of reactive oxygen species [ 223 ]. In addition, LC reduces lipid peroxidation by facilitating the transport of long-chain fatty acids into the mitochondria to generate ATP for the cell [ 224 ]. It was demonstrated that LC could also repair oxidative damage and regenerate endogenous antioxidant activity [ 225 , 226 ].…”
Section: Natural Products and Compounds As Possible Agents To Counter...mentioning
confidence: 99%
“…The protective effects of LC are due to its antioxidant properties which work as scavengers of reactive oxygen species [ 223 ]. In addition, LC reduces lipid peroxidation by facilitating the transport of long-chain fatty acids into the mitochondria to generate ATP for the cell [ 224 ]. It was demonstrated that LC could also repair oxidative damage and regenerate endogenous antioxidant activity [ 225 , 226 ].…”
Section: Natural Products and Compounds As Possible Agents To Counter...mentioning
confidence: 99%
“…When the accumulation of reactive oxygen molecules reaches a certain level, the antioxidant system of the sperm is disrupted, resulting in lipid peroxidation damage and subsequent irreversible negative effects on sperm vitality, viability, and quality [ 7 ]. Studies have shown that exogenous antioxidant substances can be added to semen diluents to reduce oxidative stress, limit the damage caused by ROS, extend sperm preservation time, and maintain quality after preservation [ 8 , 9 ]. Currently, the exogenous antioxidants used in semen preservation can be mainly divided into antioxidant enzymes, vitamins, amino acids, and plant extracts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%